Fourier transform holography at the wavelength limit - Tadesse, G. K.; Eschen, W.; Klas, R.; Hilbert, V.; Schelle, D.; Nathanael, A.; Zilk, M.; Steinert, M.; Schrempel, F.; Pertsch, Thomas; Tu¨nnermann, A.; Limpert, Jens; et al. (Optics InfoBase Conference Papers, 2018)
We present a table-top Fourier transform holography experiment that achieved a recordhigh resolution of 34 nm. By employing phase retrieval techniques, the resolution was improved to 23 nm (< 1.3 λ) limited by wave-guiding effects.
CRIS-Team Scopus Importer:2023-04-20